1988
DOI: 10.1177/104438948806900803
|View full text |Cite
|
Sign up to set email alerts
|

Who's Serving the Homeless?

Abstract: Although responses to homelessness have increased dramatically, little attention has been paid to the service providers who work with this population. The authors present descriptive data on the characteristics of service providers, their job functions and roles, and job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The measure involvement with clients with severe and persistent mental illness (SPMI) is based on Hagen and Hutchison's (1988) description of symptoms and behaviors related to having severe mental illness. This scale comprises eight items that reflect the workers' perception about the extent to which they work with clients who suffer from symptoms related to severe mental illness, and engage in socially unaccepted behaviors which are also related to mental illness.…”
Section: Methodsmentioning
confidence: 99%
“…The measure involvement with clients with severe and persistent mental illness (SPMI) is based on Hagen and Hutchison's (1988) description of symptoms and behaviors related to having severe mental illness. This scale comprises eight items that reflect the workers' perception about the extent to which they work with clients who suffer from symptoms related to severe mental illness, and engage in socially unaccepted behaviors which are also related to mental illness.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, surprisingly little attention has been given to the educational background, training, and support of those implementing programs for homeless persons. A large number of these staff members, who spend much of their time providing direct service to clients, are relatively inexperienced and have had minimal education or training ( Hagen & Hutchison, 1988), yet few resources are devoted to remedying the situation or providing them with support. All too often, staff members with limited onsite and community resources and little or no training, are called on to respond not only to families' need for housing and income assistance, but also to a wide range of health and psychosocial problems associated with homelessness.…”
Section: Staffng Patterns Training and Supportmentioning
confidence: 99%
“…Predictably, many programs describe stafiing problems that reflect these issues (Better Homes Foundations, 1990). In the only published survey describing shelter staff characteristics, Hagen and Hutchison (1988) found that 70% of the shelter-staff respondents had a bachelor's degree or less; 66% earned less than $15,000 per year; and almost half had less than one year's experience working with homeless people.…”
Section: Staffng Patterns Training and Supportmentioning
confidence: 99%
“…Given the lack of proactive care for homeless people and their high morbidity, they stand out as frequent attenders when they do access healthcare services, which can create ambivalent staff attitudes to this needy underclass. Staff treating the homeless had a 25% prevalence of stress and burnout in a study in upstate New York, USA (Hagen & Hutchison 1988). In residential projects in London, UK, Hinton (1997) described the hopelessness expressed by health professionals and lay staff in relation to the intractable needs of their clients.…”
Section: Introductionmentioning
confidence: 99%